Watching video of discrete maneuvers yields better action memory and greater activation in the middle temporal gyrus in half-pipe snowboarding athletes - Chen, Y.; Wang, Y.; Zhao, Q.; Wang, Y.; Lu, Y.; Zhou, C. (Neuroscience Letters, 2020)
Although motor performance training often involves action observation, it has been controversial whether individual aesthetic sport athletes benefit more from watching videos of discrete maneuvers (DMs) or continuous runs (CRs). In the present study, half-pipe snowboarding athletes completed a visual 2-back task with DM and CR conditions. To explore the neural mechanisms of action memory processing, brain hemodynamic activity during the task was monitored with functional near-infrared spectroscopy (fNIRS). Compared to watching CR videos, watching DM videos tended to yield better action memory performance and greater activation in the middle temporal gyrus to these athletes, suggesting that watching DM videos may have a tendency to improve action memory more effectively. Evidence of two pathways underlying half-pipe snowboarding action processing was obtained. Watching of CR videos and watching of DM videos might be associated with activation of more sensorimotor regions and more semantic regions, respectively, during memory consolidation.